Vowel Consumption for Assimilation: Between the Criteria of Optimality Theory and Ibn Jinni in His Book “Al-Muhtasib - Majeed, Wisam Jasim; Abad, Dr. Marzie; Faisal, Dr. Muhannad Dhiab (Thi Qar Arts Journal, 2024)
This research aims to examine the phenomenon of vowel consumption for assimilation, whether it is a case vowel or a building vowel, in the anomalous Quranic readings in Ibn Jinni’s book “Al-Muhtasib” according to two criteria. The first follows the path of the old linguistic study, represented by the view of Abu Al-Fath Ibn Jinni and what he sees as a reason for dropping the grammatical or structural entitlement. The second follows the path of the Optimality Theory (OT) as a modern theory that encompasses the field of language in general, including syntax, morphology, and phonology. The research then explains each approach’s method in directing these usages, as they deviate from the well-known established rules or are considered residual linguistic outputs from native speakers. The research aims to identify the points of agreement and disagreement in the method of direction or acceptance of these inputs. Ibn Jinni considers assimilation a directive reason for accepting these inputs, while the Optimality Theory (OT) addresses these usages from a broader and more comprehensive perspective. Ultimately, both criteria agree on accepting these performances, although they differ in their approach.